1975
DOI: 10.1002/pol.1975.170130116
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization behavior of vinylimidazolium salts

Abstract: Copolymerization studies of cationic monomers have been reported in the literature to yield wide variations in reactivity ratios and Q–e values, depending on the comonomer and the nature of the solvent. In this work are presented the copolymerization characteristics of a variety of vinylimidazolium salts in both water and ethanol solution. From these studies, the effect of solvent polarity, of substitution at the imidazolium 2‐position, of the type of counterion, and of the hydrophilic–hydrophobic character of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Importantly, this "head" type vinyl polymer without main chain spacer is not water-soluble and thus not a "true" polysoap, but forms only metastable aqueous solutions (see Sect 2.2.4). Similar results were reported for alkylated poly(vinylimidazoles) such as 26 [347]. It may be speculated that such solutions represent rigid "molecular latexes" rather than flexible "polymeric micelles", and further studies on such systems would be most interesting.…”
Section: Viscositysupporting
confidence: 79%
“…Importantly, this "head" type vinyl polymer without main chain spacer is not water-soluble and thus not a "true" polysoap, but forms only metastable aqueous solutions (see Sect 2.2.4). Similar results were reported for alkylated poly(vinylimidazoles) such as 26 [347]. It may be speculated that such solutions represent rigid "molecular latexes" rather than flexible "polymeric micelles", and further studies on such systems would be most interesting.…”
Section: Viscositysupporting
confidence: 79%
“…The inner structure of PIL nanoparticles is related to the inherent character of ILMs, which bear a very hydrophilic ion liquid head (ionic pair of an imidazolium cation and a Br anion), and a long hydrophobic alkyl tail that may crystallize. It is true that under the present polymerization conditions the amphiphilic monomers formed micelles, 37,38 with the alkyl chains building up the core and the vinylimidazolium moieties pointing out into water. However, the PIL nanoparticles are no more simple micelles of core-shell structures, because their size (20-40 nm) is far beyond that of a micelle built up from these ILMs; thus some more organized substructure rather than a single micellar structure must exist within these nanoparticles.…”
Section: Resultsmentioning
confidence: 98%
“…21,37,38 They observed that the solution behavior of the as-synthesized polymers was directly related to the length scale of the alkyl chains. After the polymerization, the polymers were fairly water-soluble for short alkyl (methyl and propyl) chains and totally insoluble for the intermediate alkyl (hexyl and heptyl) chains; interestingly, for even longer alkyl (decyl and hexadecyl) chains, a stable dispersion together with 30 wt % of precipitate was obtained.…”
Section: Resultsmentioning
confidence: 98%
“…In can also be possible that the resultant zwitterion due to the polarization of vinylic double bond initiating the chain propagation. Therefore, the polymerization reaction may either proceeds via unimolecular mechanism, bimolecular mechanism or a combination of both ,. Though, during polymerization, the vinyl pyridine precursor is present in the reaction mixture in sufficient amount yet cannot compete with the quaternary pyridinium salt due to the fact that the vinylic double bond of vinyl pyridine exhibits more electron cloud compared to the pyridinium salts.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the presence of an IL moiety in the repeating unit of the polymer chains some IL properties (IL chemistry and physics) are integrated into the polymeric architecture . The PILs exhibit some unique properties of ionic liquid such as ionic conductivity, thermal conductivity, tenability, chemical stability blended with the intrinsic polymeric properties . The synergistic effect can positively enable new functions and improve the performance of some polymer materials.…”
Section: Introductionmentioning
confidence: 99%